A cell-based smoothed discrete shear gap method (CS-FEM-DSG3) for dynamic response of laminated composite plate subjected to blast loading - Hau, Dang Trung; Hanh, Nguyen Thoi My; Trung, Nguyen Thoi (Vietnam Journal of Mechanics, 2015)
The paper investigates the dynamic response of laminated composite plate under the effect of blast loading. The cell-based smoothed discrete shear gap method (CS-FEM-DSG3) based on the first-order shear deformation theory (FSDT) and the equivalent layer theory (ELT) is used to model the behavior of the laminated composite plate. The blast loading is simulated by a time diagram of rectangular, triangular, exponential, or sinusoidal shape. The effects of the number of layers and fiber orientation to the displacement and stress fields of the laminated composite plate are discussed. Numerical results demonstrated the accuracy and reliability of the present method compared with previous published methods.